Design of the general concept of regulated inactivation of the gene shikimatkinase for modification of the shikimat way in bacteria Bacillus subtilis - Chao, Yu; Shonina, Maria Y.; Lahodzich, Aliaksei V. (Experimental Biology and Biotechnology, 2018)
In this work demonstrated the possibility of the transformation strains of B. subtilis used to create strains-producers of shikimic acid. For 6 strains of B. subtilis, with the ability to increased synthesis of tryptophan, produced amplicons region of the genome containing genes tmrB and aroI. RFLP-analysis of the received amplicons showed their genetic polymorphism, which may be the result of mutagenesis used when receiving strains-producers of tryptophan. Based on the PCR method designed a system for fast screening of transformants for the presence of recombination and genome rearrangements presence integrative structure comprising bacterial strains used chromosomes from transformants.